Patient preferences for inflammatory bowel disease treatments: protocol development of a global preference survey using a discrete choice experiment - Schoefs, Elise; Vermeire, Séverine; Ferrante, Marc; Sabino, João; Verstockt, Bram; Avedano, Luisa; De Rocchis, Maria Stella; Sajak-Szczerba, Magdalena; Saldaña, Roberto; Straetemans, Noortje; Vandebroek, Martina; Janssens, Rosanne; et al. (Frontiers in Medicine, 2024)
Background: As the therapeutic landscape for inflammatory bowel disease (IBD) continues to expand, a need exists to understand how patients perceive and value different attributes associated with their disease as well as with current and emerging treatments. These insights can inform the development and regulation of effective interventions for IBD, benefiting various stakeholders including healthcare professionals, drug developers, regulators, Health Technology Assessment bodies, payers, and ultimately patients suffering from IBD. In response to this, the present patient preference study was developed with the aim to 1) determine the relative preference weights for IBD treatment and disease related attributes, and 2) explain how preferences may differ across patients with different characteristics (preference heterogeneity). Methods: The patient preference study (PPS) was developed through an 8-step process, with each step being informed by an advisory board. This process included: 1) stated preference method selection, 2) attribute and level development (including a scoping literature review, focus group discussions, and advisory board meetings), 3) choice task construction, 4) sample size estimation, 5) survey implementation, 6) piloting, 7) translation, and 8) pre-testing. The resulting discrete choice experiment (DCE) survey comprises 14 attributes with between two and five varying levels. Participants will answer 15 DCE questions with a partial profile design, where each of the choice questions encompasses two hypothetical treatment profiles showing four attributes. Additionally, questions about patients' socio-demographic and clinical characteristics, as well as contextual factors are implemented. The survey is available in 15 different languages and aims to minimally recruit 700 patients globally. Discussion: This protocol gives valuable insights towards preference researchers and decision-makers on how PPS design can be transparently reported, demonstrating solutions to remaining gaps in preference research. Results of the PPS will provide evidence regarding the disease and treatment related characteristics that are most important for IBD patients, and how these may differ across patients with different characteristics. These findings will yield valuable insights applicable to preference research, drug development, regulatory approval, and reimbursement processes, enabling decision making across the medicinal product life cycle that is aligned with the true needs of IBD patients.